An Observational Study of Sexual Assault Statistics in Karachi, Pakistan - Mehreen Fatima, Ramlah Naz, Summaiyya Waseem, Farah Waseem, Raffat Rasool, Ramsha Urooj Baig (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Rape against women has been a prevalent issue in Pakistan ever since its founding, with 11 reported cases daily. A bill, known widely as the Protection of Women’s Act, 2006 was approved to ensure a secure environment for the women of Pakistan. Aim: To observe and analyze Zina-Bil-Jabr cases registered after the legislation of Protection of Women’s Act, 2006. Methodology: In this retrospective observational study, data were collected from three main medico-legal centres associated with the Police Surgeon Office in Karachi from 2005 to 2021. A total of 6,580 rape cases were brought to the medico-legal centres, with 2717 of them being the offender and 3863 of them being the victims. Result: Protection of Women’s Act, 2006, a downfall was observed in the cases till 2010, when the lowest number of cases of all years were registered as 66, while after that, an upward trajectory has been witnessed with a total of 902 cases in 2021, the highest of all recorded ones. Conclusion: The current status of rape victims in the country is alarming and points out the flaws in the practical application of the laws. Keywords: Sexual assault, Rape victims, Zina-Bil-Jabr